2010
DOI: 10.1074/jbc.m110.148650
|View full text |Cite
|
Sign up to set email alerts
|

Basis for MAP4 Dephosphorylation-related Microtubule Network Densification in Pressure Overload Cardiac Hypertrophy

Abstract: Increased activity of Ser/Thr protein phosphatases types 1 (PP1) and 2A (PP2A) during maladaptive cardiac hypertrophy contributes to cardiac dysfunction and eventual failure, partly through effects on calcium metabolism. A second maladaptive feature of pressure overload cardiac hypertrophy that instead leads to heart failure by interfering with cardiac contraction and intracellular transport is a dense microtubule network stabilized by decoration with microtubule-associated protein 4 (MAP4). In an earlier stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 48 publications
1
39
0
Order By: Relevance
“…We therefore asked whether a directionally opposite phosphatase dysregulation from that seen in Alzheimer's disease could be responsible for the site-specific MAP4 dephosphorylation that appears to be responsible for microtubule stabilization in pathological cardiac hypertrophy. Our recent data indicate that such is the case, since increased activity of the predominant myocardial protein phosphatases, both that of PP1 and especially that of PP2A, is a striking and persistent feature of severe pressure overload hypertrophy (7). Finally, in asking what is responsible for persistent activation of PP2A in this setting, the observation Fig.…”
Section: Cause(s) Of Microtubule Network Densification-map4 Binding Tmentioning
confidence: 98%
See 3 more Smart Citations
“…We therefore asked whether a directionally opposite phosphatase dysregulation from that seen in Alzheimer's disease could be responsible for the site-specific MAP4 dephosphorylation that appears to be responsible for microtubule stabilization in pathological cardiac hypertrophy. Our recent data indicate that such is the case, since increased activity of the predominant myocardial protein phosphatases, both that of PP1 and especially that of PP2A, is a striking and persistent feature of severe pressure overload hypertrophy (7). Finally, in asking what is responsible for persistent activation of PP2A in this setting, the observation Fig.…”
Section: Cause(s) Of Microtubule Network Densification-map4 Binding Tmentioning
confidence: 98%
“…that activity of an upstream multifunctional enzyme, Pak1, is increased in early cardiac hypertrophy (33) provided another important insight, since in our hands Pak1 activity is persistently increased in severe pressure overload hypertrophy and overexpression of Pak1 in normal cardiomyocytes reproduces the hypertrophic microtubule phenotype (7).…”
Section: Cause(s) Of Microtubule Network Densification-map4 Binding Tmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when phosphorylated at Ser-924 of the KXGS motif (equivalent to Ser-914 in mice) within the MT binding domain, this interaction is inhibited and MT stability is reduced (4). Cheng et al (3) showed that increased phospha- tase activity during pressure overload results in dephosphorylation of MAP4 Ser924 , thereby promoting MT assembly and stabilization. We find that activation of AMPK increases MAP4 phosphorylation at the analogous site in rat cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%